2019
DOI: 10.3390/met9121253
|View full text |Cite
|
Sign up to set email alerts
|

An Ultra-Fast Annealing Treatment by Electropulsing during Pure Copper Wire Drawing

Abstract: The influence of electropulses in situ on the drawing process of copper wires was investigated, with the aim of avoiding time consuming annealing thermal treatments. It was found that with the application of electropulses, tensile and drawing forces were reduced and the plasticity of the wire was improved. Meanwhile, compared with conventional drawing, hardness decreased. With the electropulsing treatment, no differences were found in the material’s resistivity. The microstructure exhibited similar grain size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…The second group consists of contributions devoted to shaping and unconventional shaping [5][6][7]. The third group includes those articles that deal with the field of heat treatment [8][9][10][11][12][13]. Perhaps the contributions could be divided in other ways, but we consider this appropriate.…”
Section: Contribution To the Special Issuementioning
confidence: 99%
See 2 more Smart Citations
“…The second group consists of contributions devoted to shaping and unconventional shaping [5][6][7]. The third group includes those articles that deal with the field of heat treatment [8][9][10][11][12][13]. Perhaps the contributions could be divided in other ways, but we consider this appropriate.…”
Section: Contribution To the Special Issuementioning
confidence: 99%
“…The influence of electropulses in situ on the drawing process of copper wires was investigated, with the aim of avoiding time consuming annealing thermal treatments. It was found that with the application of electropulses, tensile and drawing forces were reduced, and the plasticity of the wire was improved [10]. A non-uniform temperature across the width of martensitic stainless-steel strips is considered to be one of the main reasons why the strip exhibits un-flatness defects during the hardening process.…”
Section: Contribution To the Special Issuementioning
confidence: 99%
See 1 more Smart Citation
“…A wide range of scientific papers concerning the generally understood process of drawing of round wires were written in the 20th and 21st centuries, both in terms of the conventional drawing process and innovative methods, such as accumulated angular drawing (AAD), which tests the influence of the linearity of dies throughout the process; drawing with the use of ultrasound; drawing with an elevated temperature of the die [ 14 ]; or drawing with the use of high-density electric current pulses [ 15 ] or annealing by electropulsing during pure copper wire drawing, which allows the annealing time during the wire drawing process of pure copper to be shortened, and thus does not strengthen the final product [ 16 ]. Lack of strain hardening during the wire drawing process has also been observed after specific heat treatment of other materials [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of works [15][16][17][18][19][20][21] on the occurrence of delamination in conjunction with the development of texture, the formation of tensile residual stress on the wire surface, the partial decomposition of cementite, and drawing conditions. To prevent the occurrence of delamination, many works about improving ductility and drawability of cold drawn wires by changing manufacturing conditions, such as the modification of pass schedule [22], the control of galvanized coating layer structure [23], and the adoption of a fast heating treatment by using electro-pulsing [24,25], have been reported. However, the occurrence of delamination is not adequate to evaluate the torsional ductility of steel wire, since the occurrence of delamination acts as a simple indicator of brittle fracture during a torsion.…”
Section: Introductionmentioning
confidence: 99%